2009
DOI: 10.1074/jbc.m109.029454
|View full text |Cite
|
Sign up to set email alerts
|

The Trehalose Pathway Regulates Mitochondrial Respiratory Chain Content through Hexokinase 2 and cAMP in Saccharomyces cerevisiae

Abstract: In yeast, trehalose is synthesized by a multimeric enzymatic complex: TPS1 encodes trehalose 6-phosphate synthase, which belongs to a complex that is composed of at least three other subunits, including trehalose 6-phosphate phosphatase Tps2 and the redundant regulatory subunits Tps3 and Tsl1. The product of the TPS1 gene plays an essential role in the control of the glycolytic pathway by restricting the influx of glucose into glycolysis. In this paper, we investigated whether the trehalose synthesis pathway c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
2
20
0
Order By: Relevance
“…Transcrip-tional analysis of a ⌬hxk2 mutant strain showed significant upregulation of genes with binding sites for Mig1 and/or Cat8 (15,20,21). In addition, Hxk2 also participates in the control of genes encoding sugar transporters (22) and genes modulating mitochondrial cytochrome content and respiratory activity (23). This is also supported by a diminished Crabtree effect in ⌬hxk2 mutants, resulting in a nearly complete respiratory metabolism at high glucose concentration (20).…”
supporting
confidence: 49%
“…Transcrip-tional analysis of a ⌬hxk2 mutant strain showed significant upregulation of genes with binding sites for Mig1 and/or Cat8 (15,20,21). In addition, Hxk2 also participates in the control of genes encoding sugar transporters (22) and genes modulating mitochondrial cytochrome content and respiratory activity (23). This is also supported by a diminished Crabtree effect in ⌬hxk2 mutants, resulting in a nearly complete respiratory metabolism at high glucose concentration (20).…”
supporting
confidence: 49%
“…It has been shown that treatment of human preadipocytes with forskolin (which leads to an overactivation of the cAMP pathway) increased mitochondrial DNA copy number (10). In yeast, there is now a growing amount of evidence showing that overactivation of the Ras/ cAMP pathway leads to an increase in the cell mitochondrial content (11)(12)(13). Yeast has three A kinase catalytic subunits, which have greater than 75% identity and are encoded by the TPK (TPK1, TPK2, and TPK3) genes (14).…”
mentioning
confidence: 99%
“…We made use of this strain in order to manipulate intracellular cAMP concentration to various extents and study the energy metabolism response to variations in the activity of the Ras/cAMP pathway. Extracellular cAMP concentrations of 1-3 mM were used that led to physiological variations of the intracellular cAMP concentration from 4 to 50 M (Table 1) (16,26,27). Under these conditions, no significant modification in cell proliferation was assessed (data not shown).…”
Section: Resultsmentioning
confidence: 99%